Effects of surface morphology and C concentration in C‐doped GaN buffer on breakdown voltage of AlGaN/GaN HEMTs on free‐standing GaN substrate. Issue 5 (12th February 2016) - Tanabe, Shinichi; Watanabe, Noriyuki; Uchida, Masahiro; Matsuzaki, Hideaki
Abstract : We report on the validity of using a C‐doped GaN buffer to achieve high‐breakdown‐voltage AlGaN/GaN high‐electron mobility transistors (HEMTs) on conductive free‐standing GaN substrates. We use trimethygallium to dope C into the buffer. We show that breakdown voltage depends not only on the C concentration of the buffer but also on the surface morphology of the HEMT structure. We demonstrate off‐state breakdown voltage of over 2 kV by controlling the C concentration of the buffer, thickness of the buffer, and the surface morphology.